2013
DOI: 10.1177/0954406213480312
|View full text |Cite
|
Sign up to set email alerts
|

Internally cooled tools and cutting temperature in contamination-free machining

Abstract: Whilst machining heat is generated by the friction inherent into the sliding of the chip on the rake face of the insert, the temperature in the cutting zone of both the insert and the chip rises, facilitating adhesion and diffusion. These effects accelerate the insert wear, ultimately undermining the tool life. Therefore, a number of methods have been developed to control the heat generation. Most typically, metal working fluids are conveyed onto the rake face in the cutting zone, with negative implications on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
1
29
0
2
Order By: Relevance
“…More details regarding suitable transformations of the response to overcome observed departures of the assumed homoscedasticity of the errors in the case of linear models are presented by Faraway (cf pages 53-58 in [23]). The parameters in Equation 8and (9) have been estimated as in the previous cases using the nlme library ( Table 3) [ Table 3 Thus there was no reason for excluding the two experimental results from the analysis. Moreover, even doing so, the resulting fitted model did not lead to significantly different estimates of the parameters.…”
Section: Modelling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…More details regarding suitable transformations of the response to overcome observed departures of the assumed homoscedasticity of the errors in the case of linear models are presented by Faraway (cf pages 53-58 in [23]). The parameters in Equation 8and (9) have been estimated as in the previous cases using the nlme library ( Table 3) [ Table 3 Thus there was no reason for excluding the two experimental results from the analysis. Moreover, even doing so, the resulting fitted model did not lead to significantly different estimates of the parameters.…”
Section: Modelling and Analysismentioning
confidence: 99%
“…Previous research in the field of indirect cooling methods has shown that it is possible to reduce significantly the cutting temperature. In particular, Ferri et al [9] compared the chip temperature in dry turning of the aluminium alloy AA6082-T6 when using conventional and internally cooled tools. Their main finding was that the internally-cooled tools appeared increasingly effective in containing the chip temperature while increasing the depth of cut.…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents the design concept, development processes, application principles for the above smart tools, for high precision and micro machining in particular. The paper also explores and discusses the implementation and application perspectives of those smart tools against the smart machining requirements from a number of industrial applications, such as micromachining maintained with constant cutting force, extrahigh speed micro drilling, and contamination-free machining of medical device or explosive materials [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial description of this type of cooling system in the 1970s, a variety of improvements have been proposed. Ferri designed an internally cooled cutting tool consisting of a modified cutting insert, cooling adapter accommodating micro-channel, and tool-holder with inlet and outlet ports [11]. Minton created a modified tool-holder with an internally cooled tool to enhance the heat transfer [12].…”
Section: Introductionmentioning
confidence: 99%